Downregulation of deoxycytidine kinase in cytarabine-resistant mantle cell lymphoma cells confers cross-resistance to nucleoside analogs gemcitabine, fludarabine and cladribine, but not to other classes of anti-lymphoma agents - Klánová, Magdalena; Lorkova, Lucie; Vit, Ondrej; Maswabi, Bokang; Molinský, Jan; Pospisilova, Jana; Vockova, Petra; Mavis, Cory; Latečková, Lucie; Kulvait, Vojtech; Vejmelkova, Dana; Jakša, Radek; et al. (Molecular cancer, 2014)
BACKGROUND: Mantle cell lymphoma (MCL) is an aggressive type of B-cell non-Hodgkin lymphoma associated with poor prognosis. Implementation of high-dose cytarabine (araC) into induction therapy became standard-of-care for all newly diagnosed younger MCL patients. However, many patients relapse even after araC-based regimen. Molecular mechanisms responsible for araC resistance in MCL are unknown and optimal treatment strategy for relapsed/refractory MCL patients remains elusive. METHODS: Five araC-resistant (R) clones were derived by long-term culture of five MCL cell lines (CTRL) with increasing doses of araC up to 50 microM. Illumina BeadChip and 2-DE proteomic analysis were used to identify gene and protein expression changes associated with araC resistance in MCL. In vitro cytotoxicity assays and experimental therapy of MCL xenografts in immunodeficient mice were used to analyze their relative responsiveness to a set of clinically used anti-MCL drugs. Primary MCL samples were obtained from patients at diagnosis and after failure of araC-based therapies. RESULTS: Marked downregulation of deoxycytidine-kinase (DCK) mRNA and protein expression was identified as the single most important molecular event associated with araC-resistance in all tested MCL cell lines and in 50% primary MCL samples. All R clones were highly (20-1000x) cross-resistant to all tested nucleoside analogs including gemcitabine, fludarabine and cladribine. In vitro sensitivity of R clones to other classes of clinically used anti-MCL agents including genotoxic drugs (cisplatin, doxorubicin, bendamustine) and targeted agents (bortezomib, temsirolimus, rituximab) remained unaffected, or was even increased (ibrutinib). Experimental therapy of immunodeficient mice confirmed the anticipated loss of anti-tumor activity (as determined by overall survival) of the nucleoside analogs gemcitabine and fludarabine in mice transplanted with R clone compared to mice transplanted with CTRL cells, while the anti-tumor activity of cisplatin, temsirolimus, bortezomib, bendamustine, cyclophosphamide and rituximab remained comparable between the two cohorts. CONCLUSIONS: Acquired resistance of MCL cells to araC is associated with downregulation of DCK, enzyme of the nucleotide salvage pathway responsible for the first phosphorylation (=activation) of most nucleoside analogs used in anti-cancer therapy. The data suggest that nucleoside analogs should not be used in the therapy of MCL patients, who relapse after failure of araC-based therapies.
Keywords: regulace genové exprese u nádorů; Animals; Drug Resistance, Neoplasm; 2D gelová elektroforéza; Antibodies, Monoclonal, Murine-Derived; Cell Line, Tumor; Blotting, Western; Vidarabine; myší monoklonální protilátky; Deoxycytidine; cytarabin; Gene Expression Regulation, Neoplastic; buněčné klony; lidé; proteomika; Antineoplastic Agents; protinádorové látky; Mice; chemorezistence; lymfom z plášťových buněk; Lymphoma, Mantle-Cell; stanovení celkové genové exprese; myši; Cytarabine; hmotnostní spektrometrie; xenogenní modely - testy protinádorové aktivity; Deoxycytidine Kinase; western blotting; deoxycytidin; Down-Regulation; Proteomics; kladribin; Electrophoresis, Gel, Two-Dimensional; deoxycytidinkinasa; Mass Spectrometry; Xenograft Model Antitumor Assays; vidarabin; Clone Cells; down regulace; Cladribine; zvířata; Gene Expression Profiling; nádorové buněčné linie; Humans